Impact of time between diagnosis to treatment in Acute Type A Aortic Dissection - Caleb R. Matthews (Nature Portfolio, 2021)
Abstract There is a paucity of data describing the effect of time interval between diagnosis and surgery for Acute Type A Aortic Dissection. We describe our 8-year experience and investigate the impact of time interval between symptom onset, diagnosis and surgery on outcomes. Retrospective single-center study utilizing our Society of Thoracic Surgeons registry and patient records. Subjects were grouped by time interval between radiographic diagnosis and surgical treatment: Group A (0–4 h), Group B (4.1–8 h), Group C (8.1–12 h), and Group D (12.1 + h). Data were analyzed to identify factors associated with mortality and outcomes. 164 patients were included. Overall mortality was 21.3%. Group C had the greatest intervals between symptom onset to diagnosis to surgery, and also the highest mortality (66.7%). Preoperative tamponade, cardiac arrest, malperfusion, elevated creatinine, cardiopulmonary bypass time, and blood transfusions were associated with increased mortality, while distance of referring hospital was not. Time intervals between symptom onset, diagnosis and surgery have a significant effect on mortality. Surgery performed 8–12 h after diagnosis carries the highest mortality, which may be exacerbated by longer interval since symptom onset. Time-dependent effects should be considered when determining optimal strategy especially if inter-facility transfer is necessary.